Capacity building for sustainable use of animal genetic resources in developing countries - a new approach - Malmfors, B.; Smalley, M.E.; Philipsson, J.; Ibrahim, H.; Andersson-Eklund, L.; Okeyo Mwai, Ally; Mpofu, N.; Rege, J.E.O. (Institut National de la Recherche Agronomique, 2002)
A new approach for capacity building, "training the trainers", addressing university faculty and other NARS scientists in developing countries, has been implemented to strengthen the sustainable use of Animal Genetic Resources (AnGR) through improved research and teaching. The project is carried out in collaboration between ILRI and SLU. It includes: (i) planning activities (questionnaires, visits and workshops), (ii) regional three-week refresher course on AnGR topics and how these can best be taught, (iii) Development of electronic training resources, including case studies, (iv) follow-up workshops, networking and evaluation. This model for capacity building is expected to substantially increase knowledge on and sustainable use of AnGR through the large number of students reached by the trained teachers/scientists.